New technologies and disability (Virtualizing the lives of people with disabilities, 2021)
The article is an introduction to a monograph devoted to showing the complex relations between new technologies and disability. On the one hand, they are seen as a tool for inclusion and emancipation, and on the other hand, they are a source of exclusion for people with disabilities. Our goal is to show the contextual relationships between technological solutions and the functioning of people with disabilities in everyday life. This topic is extremely important today because in connection with the COVID-19 epidemic, the role and importance of modern technologies has increased. This was due to the necessity to transfer many daily activities to virtual space. These changes had significant consequences for people with disabilities who were affected by limitations in movement, access to medical care and education and the possibility of exercising their rights to support in independent and independent life, and had to transfer their activities to a virtual space within a very short time.